PENILAIAN PERBANDINGAN KESTABILAN LERENG BATUAN MENGGUNAKAN GENERALIZED ANISOTROPIC DAN JOINT NETWORK - Akbar, Wahyu Nusantara; Barlian Dwinagara; Singgih Saptono; Dahono Haryanto; Shofa Rijalul Haq; Bagus Wiyono; Oktarian Wisnu Lusantono (Indonesian Mining Journal, 2025)
Rock slope stability analysis in a geotechnical study is an important issue in mining engineering. Kinematic analysis is a well-known method to determine potential failures of the rock slope based on structural orientations, but it sometimes disregards the structural properties information. Structural properties are often known as the highly interpreted domains in rock slope engineering; thus, simplification was made for the analysis. Simplification may lead to vague conditions of analysis and reduce its accuracy. Therefore, the aims of this research is to assess the effect of rock structure properties such as heterogeneity, discontinuity, and anisotropic properties of the rock mass. The assessment conducted using the limit-equilibrium method employed the Generalized Anisotropic (GA) material model were compared with finite element method (FEM) using the shear strength reduction (SSR) method employing the joint network rock mass model. The analysis results show that an actual rock slope with a generalized anisotropic material model in the LEM analysis and joint network material model in the FEM analysis is stable with Safety Factor > 1, and the maximum strain model is less than the minimum strain threshold (maximum strain < 0.1). Combining rock slope stability analysis methods aims to produce accurate and representative results regarding the rock mass' condition. This research improves the interpretation of rock slope stability analyses, resulting in a more accurate estimation of the factor of safety (FOS).